Pengaruh Terapi Musik terhadap Kemampuan Anak dengan Autis dalam Memperhatikan dan Berkomunikasi: A Literatute Review - Dian Perdana; Fitri Mandasari (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Background: The difficulty of focusing joint attention and developing communication by children with autism causes children with autism to be less able to socialize with peers so that it has an impact on the desire of parents to get all kinds of therapy to improve children's ability to interact with people around them. One of the therapies used by therapists is music therapy. The purpose of this study is to review some of the literature that contains the effectiveness of music therapy on attention and communication in children with autism that can be applied effectively and have clinical uses. Objective: To describe the effect of music therapy on attention and communication skills of children with autism. Methods: The sources of the articles used were obtained from searches through Google Scholar, and Pro Quest from 2006 to 2015. Once obtained, the articles were then assessed until the stage of making a literature review. Through keywords according to the topic and obtained 3 articles that were reviewed. Results: This review resulted in the effectiveness of music therapy on attention and communication skills of children with autism. Conclusion: Music therapy can improve and improve the ability of children with autism in paying attention and communicating.